Dyslipidaemia in Cortical Versus Subcortical Infarction - Sarker, Tarun Kanti; Kuddus, Md Ruhul; Khan, Md Rezaul Karim; Ullah, AKM Anwar; Islam, Md Rafiqul; Haque, Anisul (Bangladesh Journal of Neuroscience, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Objectives: The aim of the study was to predict risk of cerebral infarction either cortical or lacunar in population having dyslipidaemia and to create awareness regarding it as a risk factor for ischaemic stroke and to take preventive measures for the prevention of a first or recurrent ischaemic stroke. Method: This study was conducted in the Department of Nurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March to October, 2006. This study included 30 acute ischaemic stroke patients diagnosed by history, clinical findings and confirmed by CT/MRI scan of head within 2 weeks of attack. Both man and woman age ranging from 40-90 years were eligible to enter into the study. The same number of age and sex matched nonstroke patients who gave blood for analysis were included as control. Result: In this study among other risk factors total serum cholesterol was raised in both cortical and lacunar infarct in 50% of cases in comparison to 33.3% controls (P<0.05). LDL-cholesterol levels were raised in both cortical and lacunar infarct in 50% of cases compared to 30% controls (P<0.05). HDL-cholesterol levels were significantly low in cases (70%) compared to control subjects (26.7%). It was significantly low in cases of cortical infarct (77.3%) compared to 50% cases of lacunar infarct (P<0.01). Serum triglyceride levels were raised in 60% of case group and 26.7% of control subjects (P<0.01). Serum triglyceride levels were raised in 54.5% cases of cortical infarcts compared to 75% cases of lacunar infarcts. Conclusion: The results indicate an association between dyslipidaemia and the risk of ischaemic stroke, specially cortical type. Dyslipidaemia more related to cortical infarct than subcortical infarct. Low level of HDL-cholesterol was related to cortical infarct but not with subcortical infarct. DOI: http://dx.doi.org/10.3329/bjn.v24i1.3037 Bangladesh Journal of Neuroscience 2008; Vol. 24 (1) : 24-33